Effects of dual-task training with ankle-foot orthosis on stroke gait. - Mizangir, Negin; Daryabor, Aliyeh; Samadian, Maryam; Shariatpanahi, Seyyed Payam; Naimi, Sedigheh Sadat (Prosthetics & Orthotics International, 2026)
Background and objective: There is limited research on the use of ankle-foot orthosis (AFO) with dual-task training. The aim of the study was to assess impact of orthotic use during dual-task training in patients who have had a stroke during walking. Study Design: The quasi-experimental study Methods: Eleven hemiplegic people after stroke, aged 35–65 years, underwent gait training with dual task for 10 daily sessions over 4 weeks, guided by a physiotherapist while wearing an AFO. Gait was measured under 2 conditions—only dual-task walking and dual-task walking with the AFO—at baseline and after 4 weeks of training using a motion capture system. The gait parameters were compared before and after intervention in each condition and between 2 walking conditions after intervention using paired t test. Results: After 4-week intervention, there was no significant difference in any gait parameters between 2 walking conditions. In dual-task walking alone, several gait parameters were significantly increased compared to baseline, including peak ankle plantarflexion angle, peak knee flexion angle in loading response, peak knee extension moment in response loading, and peak hip flexion moment in preswing. In dual-task walking with AFO, peak knee flexion angle and peak knee and hip extension moments in loading response phase were significantly increased after intervention compared to baseline. Conclusions: Although the dual-task training has had a positive effect on some aspects of gait kinetics and kinematics in patients who have had a stroke, the AFO had no additional effect on dual-task walking.